A novel binuclear iron(III)-salicylaldazine complex; synthesis, X-ray structure and catalytic activity in sulfide oxidation. (1st June 2020) - Mesbahi, Elnaz; Bagherzadeh, Mojtaba; Amini, Mojtaba; Akbari, Ali; Ellern, Arkady; Woo, L. Keith
Graphical abstract: The oxidation of sulfides to produce sulfoxides in the presence of a novel binuclear iron(III)-salicylaldazine complex were studied. Abstract: A novel binuclear iron(III)-salicylaldazine complex has been synthesized and characterized by various techniques such as IR and UV–Vis spectroscopy and X-ray crystallography. The catalytic oxidation of sulfides in the presence of the aforementioned complex was explored at room temperature using urea hydrogen peroxide (UHP) as an oxidant. Effects of different reaction conditions consisting catalyst and oxidant amount, solvent effect and reaction time on the catalytic activity and selectivity in the reaction of methylphenylsulfide oxidation has been surveyed. Perfect selectivity toward sulfoxide was achieved after 15 min in CH3 CN by choice of a properly optimized reaction condition.